Plastics - Baldivia, Aaron Fernando III; Laguinia, Elena; Ortega, Ma. Lea; Syho, Edmund (College of Engineering, 1989)
A proposed plant for the manufacture of High-density polyethylene having an annual production of 3000 MT has been designed for future establishment. This plant is to be located near the Philippine National Oil Company in Limay, Bataan. The product obtained from this plant is High-density polyethylene in pellet form. The land area necessary for the establishment of this plant is 5,400 square meters. The total capital investment is P 348,854,496 of which P 116,961,957 is the fixed capital investment and P 231,892,539 are the operational costs. The profit per year before taxes is roughly P 330,902,140. Pay-off time is estimated to be 0.3587 years or 4.3 months.